Analisis Variasi Kalimat Dan Jenis Klausa Pada Teks Biografi Siswa Kelas Viii Di Smp Negeri 2 Sidoharjo Sragen - Lestari, Riyana Lili, Dra,Atiqa Sabardila,M.Hum (2016)
The purpose of this study is to describe sentence of variations and types of clause in the biographies text of VIII class in SMP N 2 Sidoharjo. This is a qualitative research. Data source a research are student biographies text of VIII class in SMP N 2 Sidoharjo. The data research is word, phrase, clause, and sentences in the students biographies text of VIII class in SMP N 2 Sidoharjo. Data collection method and techniques use are refer to method and tapping of techniques, then further more refer to the involved free conversation and record techniques. Data analysis used is apportion and equal method. The data analysis techniques using sorting technique decisive element with referential power, then proceed with the appeal circuit techniques to distinguish. As for using the direct elements techniques, and then followed by vanished, replace, insert, change intention, and expand techniques. The result of this study sentences of variation indicate as in the biographies text written by student vary variation. The sentences of variaions that are use inside, (a) sentence variation in order, consist of 67,4% usual sequence sentences and 32,6% sentences invertion, (b) sentence variation of intonation, consist of 100% news sentences, (c) sentence of variation passive-active in the form of 85,60% active sentences, 11,30% passive sentences, and 3,10% active-passive sentences, and (d) sentence variation of short-long the are 58,80% short and 41,20% long sentences. As for the result of this study types of clause that are use long sentences in the biographies text indicate as follow, (a) 32 complete clause, (b) 24 uncomplete clause, (c) 47 positive clause, (d) 8 negative clause, (e) 45 verb clause, (f) 1 noun clause, and (g) 8 preposition clause. Keyword: biographies text, sentence of variation, types of clause